(untitled) (Actualizaciones en Sida e Infectología, 2022)
During the COVID-19 pandemic, health personnel (HP) faced changes in their working conditions due to exposure to the virus and increased demand for attention. This study inquires on the experiences and perceptions of HP in Argentina about the implementation of protocols for their protection. A survey including information on sociodemographic characteristics, protocols, resources and psychological aspects was performed for HP all over the country. Two thousand and ten surveys were analyzed: 76.4% female, mean age 43 years old, 35% physician, 72.7% public institutions. Hours of work increased for 37.2%, 22.5% had at least one risk factor, of which 20.4% had leave or re-assigned tasks. Protocols about use of personal protective equipment (PPE) were established by 91% of institutions and less frequently about other topics. Clarity of protocols was well valueted, and in 60.8% of cases trainament was performed. Approval about access and quality of PPE was variable, with better performance on private institutions. 60.4% HP had to obtain PPE by their own means. 48.4% participants followed protocols on PPE, being this variable according to groups of risk. The global index for institutional valuation was 6.45/10 (CI 95%, 6.38-6.53). HCP expressed fear or anxiety in 87.2% cases, and this was related to worse communication with superiors and worse institutional valuation. This study raises difficulties on the implementation of new protocols and the need to reinforce efforts on resources and institutional organization, to improve working conditions for HP.